Calculations of the Transition Energies and Oscillator Strengths for $Cu^{26+}$ Ion (Journal of Atomic and Molecular Sciences, 2018)
Non-relativistic energies of $1s^22s$ and $1s^2np$ $(≤ 9)$ states for $Cu^{26+}$ ion arecalculated by using the full-core plus correlation method. For $1s^22s$ and $1s^22p$ states,relative discrepancies between our results and high precision results of Yan et al. arewithin 0.1 ppm. By taking account of the first-order corrections to the energy fromrelativistic and mass-polarization effects, the higher-order relativistic contribution andQED correction to the energy are estimated under a hydrogen-like approximation. Thetransition energies, wavelengths and oscillator strengths for the $1s^22s-1s^2np$ transitionsof the ion are calculated. The results obtained by the three forms are in goodagreement with each other.